2013
DOI: 10.1088/0953-4075/46/3/035501
|View full text |Cite
|
Sign up to set email alerts
|

Unitary quantum phase operators for bosons and fermions: a model study on the quantum phases of interacting particles in a symmetric double-well potential

Abstract: Abstract. We introduce unitary quantum phase operators for material particles. We carry out a model study on quantum phases of interacting bosons in a symmetric double-well potential in terms of unitary and commonly-used non-unitary phase operators and compare the results for different number of bosons. We find that the results for unitary quantum phase operators are significantly different from those for non-unitary ones especially in the case of low number of bosons. We introduce unitary operators correspond… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
3
1

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(17 citation statements)
references
References 45 publications
0
17
0
Order By: Relevance
“…Here we consider Barnett-Pegg [2] type quantum phase operators for matterwave of few bosons or fermions. Matter-wave phase operators were first introduced in 2013 [4]. It is shown that [4,5], for a low number of bosons or fermions, unitary nature of the phase-difference operators is important.…”
Section: Phase-operators: a Brief Reviewmentioning
confidence: 99%
See 3 more Smart Citations
“…Here we consider Barnett-Pegg [2] type quantum phase operators for matterwave of few bosons or fermions. Matter-wave phase operators were first introduced in 2013 [4]. It is shown that [4,5], for a low number of bosons or fermions, unitary nature of the phase-difference operators is important.…”
Section: Phase-operators: a Brief Reviewmentioning
confidence: 99%
“…Matter-wave phase operators were first introduced in 2013 [4]. It is shown that [4,5], for a low number of bosons or fermions, unitary nature of the phase-difference operators is important. For large number of photons or quanta, the non-unitary Carruthers-Nieto [13] phase-difference operators yield almost similar results as those due to Barnett-Pegg type unitary operator.…”
Section: Phase-operators: a Brief Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…In terms of number and quantum phase variables, the number and phase squeezing properties are also different in two cases [26]. Quantum phase fluctuations are calculated using the recently introduced quantum mechanical phase operators for matter-waves [27].…”
Section: Introductionmentioning
confidence: 99%